Efektivitas dan Kontribusi Penerimaan Pendapatan Asli Daerah (PAD) dan Dana Perimbangan terhadap Pendapatan Daerah Kabupaten Barito Utara Tahun 2016-2020 - Suratmi, Suratmi; Nur, Muhammad Anshar (PPJP Universitas Lambung Mangkurat, 2023)
This study aims to analyze how the growth rate of PAD revenue and PAD sources is, find out the low contribution of PAD sources and analyze the effectiveness and contribution of PAD and Balancing Fund revenues to North Barito Regency Regional Income in 2016-2020. This study uses descriptive quantitative methods using primary data sources and secondary data. The results showed that: (1) The growth rate of PAD was 8%, and the sources of PAD were taxes 16%, user fees 13%, legitimate wealth management 11% and other legitimate PAD 6%, all with unsuccessful criteria. (2) Regional retribution revenue is a source of PAD revenue with the lowest contribution of 9.17% (very low) in 2016-2020. (3) The average effectiveness of PAD in 2016-2020 is 96.46% (effective), and the average effectiveness of balancing funds in 2016-2020 is 99.88% (effective). (4) The average contribution of PAD revenue to regional income in 2016-2020 is 5.93% (very low) and the average contribution of balancing funds to regional income in 2016-2020 is 82.88% (very good).